2015
DOI: 10.1021/la5049024
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Water-in-Water Pickering Emulsions

Abstract: The structure and stability of water-in-water emulsions was investigated in the presence of spherical, pH-sensitive microgels. The emulsions were formed by mixing aqueous solutions of dextran and PEO. The microgels consisted of cross-linked, synthetic polymers with a radius that steeply increased from 60 to 220 nm with increasing pH within a narrow range around 7.0. At all pH values between 5.0 and 7.5, the microgels were preferentially situated at the interface, but only in a narrow range between pH 7.0 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 31 publications
2
69
0
2
Order By: Relevance
“…It was suggested that this allowed the appearance of a channel between adjacent droplets and that subsequently particles were ejected from the surface by the shear forces during the coalescence process. It was reported that the structure of particle stabilized W/W emulsions is the same after hand shaking as after more energetic mixing methods (Balakrishnan et al, 2012;de Freitas, Nicolai, Chassenieux and Benyahia, 2016;Nguyen, Nicolai and Benyahia, 2013;Nguyen, Wang, Saunders, Benyahia and Nicolai, 2015) . In addition, for the rather viscous mixture of amylose and xyloglucan in the presence of protein microgels (de Freitas et al, 2016) it was observed by microscopy that after shaking initially naked droplets of the dispersed phase are formed that coalesce and are progressively covered with particles.…”
Section: Model Systemsmentioning
confidence: 95%
See 1 more Smart Citation
“…It was suggested that this allowed the appearance of a channel between adjacent droplets and that subsequently particles were ejected from the surface by the shear forces during the coalescence process. It was reported that the structure of particle stabilized W/W emulsions is the same after hand shaking as after more energetic mixing methods (Balakrishnan et al, 2012;de Freitas, Nicolai, Chassenieux and Benyahia, 2016;Nguyen, Nicolai and Benyahia, 2013;Nguyen, Wang, Saunders, Benyahia and Nicolai, 2015) . In addition, for the rather viscous mixture of amylose and xyloglucan in the presence of protein microgels (de Freitas et al, 2016) it was observed by microscopy that after shaking initially naked droplets of the dispersed phase are formed that coalesce and are progressively covered with particles.…”
Section: Model Systemsmentioning
confidence: 95%
“…This must change the wetting characteristics of the particles, plus their tendency to aggregate. It is therefore perhaps easier to understand particlecontrol of W/W emulsions where neither of the biopolymers is surface active, like the dextran-PEO systems extensively studied by Nguyen et al (2015). In this case there is also the possibility of introducing protein particles (insoluble solid or microgel particles) as an alternative and distinct stabilizing entity, as these workers have done.…”
Section: Food Grade W/w Emulsionsmentioning
confidence: 99%
“…This de-mixing generates aw ater-inwater emulsion (an recent example of which is given by Nguyen et al), [14] suggesting that self-assembly could occur if the different polymers were covalently attached to each other. Ther esulting water-in-water-in-water systems (implying that the membrane itself would also be mostly composed of water) would effectively contain separate but adjacent aqueous phases between which free transport would be possible.W e hypothesize that the resulting self-assembly mechanism, driven by competition for water, could extend the capability for self-assembly beyond the standard amphiphilic structures.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Üblicherweise wird angenommen, dass diese Systeme notwendigerweise amphiphil sein müssen:h ergestellt aus hydrophil-hydrophoben Blockcopolymeren. Diese Entmischung kreiert eine Wasser-in-Wasser-Emulsion (ein aktuelles Beispiel stammt von Nguyen et al [14] ), was nahelegt, dass auch Selbstorganisation eintreten kann, sofern beide Subphasen miteinander kovalent verknüpft sind. [10] Dieser Vorgang führt zu wohldefinierten Strukturen, aber die resultierenden Systeme sind immer beschränkt durch die Grenzen, die die Amphiphilie setzt, und die entstehende hydrophobe Membran repräsentiert eine (gewollte oder auch in diesem Umfang nicht ge-wollte) Barriere für den Tr ansport hydrophiler Substanzen.…”
Section: Selbstorganisationsprozesse Sind Entscheidend Für Dasunclassified